Love for the Ahl al-Bayt (AS) from the perspective of the Qur'an and Sunnah by explaining the verse of Mawdat - yosef mogaddasi; Amir Mahmoudi (مطالعات تطبیقی فقه و اصول مذاهب)
Anas with the Holy Quran is full of the care of God Almighty for "Dhi Al-Qarbi and Ahl al-Bayt (peace be upon them)". According to the authentic and agreed upon hadiths about the Ahl al-Bayt (AS) by the Holy Prophet (PBUH), both in the form of holy hadiths and the prophetic hadiths mentioned in the text of the article, all indicate the need for love for the Ahl al-Bayt by all Muslims. The purpose of this research is to process the love for the Ahl al-Bayt (AS) from the perspective of the Qur'an and the Sunnah of the Holy Prophet (PBUH) by explaining the verse of Maudut. According to the findings of this article, according to several narrations that have been introduced through the first-hand texts of Shiites and Sunnis, the examples in question of the verse of Mawdat are the same (pure Imams (as)). Therefore, love for the pure Imams and love for those rulers is a religious necessity and a public duty for all Muslims. The method used is library study and the use of Quranic verses and original religious texts in a descriptive-analytical and qualitative manner.